Distribution of Breeding Shorebirds on the Arctic Coastal Plain of Alaska - Johnson, James A.; Lanctot, Richard B.; Andres, Brad A.; Bart, Jonathan R.; Brown, Stephen C.; Kendall, Steven J.; Payer, David C. (ARCTIC, 2009)
Available information on the distribution of breeding shorebirds across the Arctic Coastal Plain of Alaska is dated, fragmented, and limited in scope. Herein, we describe the distribution of 19 shorebird species from data gathered at 407 study plots between 1998 and 2004. This information was collected using a single-visit rapid area search technique during territory establishment and early incubation periods, a time when social displays and vocalizations make the birds highly detectable. We describe the presence or absence of each species, as well as overall numbers of species, providing a regional perspective on shorebird distribution. We compare and contrast our shorebird distribution maps to those of prior studies and describe prominent patterns of shorebird distribution. Our examination of how shorebird distribution and numbers of species varied both latitudinally and longitudinally across the Arctic Coastal Plain of Alaska indicated that most shorebird species occur more frequently in the Beaufort Coastal Plain ecoregion (i.e., closer to the coast) than in the Brooks Foothills ecoregion (i.e., farther inland). Furthermore, the occurrence of several species indicated substantial longitudinal directionality. Species richness at surveyed sites was highest in the western portion of the Beaufort Coastal Plain ecoregion. The broad-scale distribution information we present here is valuable for evaluating potential effects of human development and climate change on Arctic-breeding shorebird populations. Les renseignements qui existent en matière de répartition des oiseaux de rivage en reproduction sur la plaine côtière de l’Arctique en Alaska sont anciens, fragmentés et restreints. Ici, nous décrivons la répartition de 19 espèces d’oiseaux de rivage à partir de données recueillies à 407 lieux de recherche entre 1998 et 2004. Cette information a été recueillie grâce à une technique de recherche consistant en une seule visite rapide durant les périodes d’établissement du territoire et de début d’incubation, ...